Characterization and evaluation of olive germplasm in southern Italy. (25th February 2013) - Di Vaio, Claudio; Nocerino, Sabrina; Paduano, Antonello; Sacchi, Raffaele
Abstract Background The southern Italian region of Campania has suitable pedo‐climatic conditions and a large varietal heritage able to produce oils with high typicality. The aim of this study was to characterize 20 cultivars belonging to Campania's olive germplasm, evaluating their vegetative and production aspects and their oil quality characteristics. The study was conducted from 2003 to 2009, observing the following aspects in six plants per variety: entry into production, vigour, ripening and drupe oil content. The following analyses were carried out on monovarietal oils, obtained by microextractor: acid composition, polyphenol content and aromatic profile. Results The agronomic results showed early entry into production for the cultivars Racioppella, Ortolana, Biancolilla and Carpellese. However, entry into production was delayed for Ritonnella, Ortice, Cornia and Rotondella. As regards vegetative behaviour, Asprinia, from the province of Caserta and Pisciottana and Carpellese, from the province of Salerno, proved the most vigorous cultivars. Conclusion Groups of similar cultivars emerged from chemical and sensory analysis of their oils, while other accessions were well characterized and separated from each other, showing a high level of diversity and specificity. © 2013 Society of Chemical Industry